Effect of workplace- versus home-based physical exercise on musculoskeletal pain among healthcare workers: a cluster randomized controlled trial - Markus D Jakobsen; Emil Sundstrup; Mikkel Brandt; Kenneth Jay; Per Aagaard; Lars L Andersen (Nordic Association of Occupational Safety and Health (NOROSH), 2015)
OBJECTIVE: Numerous studies has shown that regular physical exercise can reduce musculoskeletal pain, but the optimal setting to achieve high adherence and effectiveness remains unknown. This study investigated the effect of workplace versus home-based physical exercise on musculoskeletal pain among healthcare workers. METHODS: The randomized controlled trial (RCT) comprised 200 female healthcare workers from 18 departments at 3 hospitals. Participants were randomly allocated at the cluster level to ten weeks of: (i) workplace physical exercise (WORK) performed during working hours for 5×10 minutes per week and up to 5 group-based coaching sessions on motivation for regular physical exercise, or (ii) home-based physical exercise (HOME) performed during leisure time for 5×10 minutes per week. Both groups received ergonomic counseling on patient handling and use of lifting aides. Average pain intensity (0-10 scale) in the low back and neck/shoulder was the primary outcome. RESULTS: Per week, 2.2 (SD 1.1) and 1.0 (SD 1.2) training sessions were performed in WORK and HOME groups, respectively. Pain intensity, back muscle strength and use of analgesics improved more following WORK than HOME (P<0.05). Between-group differences at follow-up (WORK versus HOME) was -0.7 points for pain intensity [95% confidence interval (95% CI) -1.0- -0.3], 5.5 Nm for back muscle strength (95% CI 2.0-9.0), and -0.4 days per week for use of analgesics (95% CI -0.7- -0.2). The effect size for between-group differences in pain intensity was small (Cohen's d=0.31). CONCLUSIONS: Workplace physical exercise is more effective than home-based exercise in reducing musculoskeletal pain, increasing muscle strength and reducing the use of analgesics among healthcare workers.